Stability analyses of residual soil slope under different rainfall conditions - Jing, Yannan (Nanyang Technological University, 2019)
Climate change contributes to the changes in rainfall patterns. Many areas are experiencing a larger amount of rainfall with a higher intensity. It results in an increase in the frequency of rainfall-induced slope failures. In geotechnical engineering practice, the rainfall loading can be considered as a parameter in triggering slope failure. However, limited studies have been conducted to identify the influence of the increase in rainfall intensity and rainfall duration due to climate change on the stability of residual soil slopes. Therefore, the objective of this project is to study the stability of residual soil slopes with different soil-water characteristic curves (SWCCs) and unsaturated shear strengths under different rainfall conditions. The scope of the project involved measurements of SWCC, saturated permeability, saturated and unsaturated shear strength of residual soils from Old Alluvium and Jurong Formation. In addition, 2-D seepage and stability analyses of unsaturated residual soil slopes were performed to investigate the variations of Factor of Safety (FoS) with respect to different rainfall conditions. The results of the study indicated the decreasing rate in FoS of the slope from Old Alluvium was higher as compared to the rate of decrease in FoS of the slope from sedimentary Jurong Formation. This was attributed to the higher permeability of the residual soil from Old Alluvium. In addition, the rate of recovery in FoS of the slope from sedimentary Jurong Formation was lower than that of the slope from Old Alluvium after rainfall stopped.